Ways to increase demand for local products, import substitutes - Olimjonov, Daler Damirovich; Kamilova, Nargiza Abdukahorovna (Science and Education, 2023)
This article analyzes the composition of the demanded imported products, the pros and cons of localizing imported goods and recommendations for improving the production of import-substituting products and their promotion in the market.